Association between prepartum vaginal temperature changes and placenta expulsion time in Holstein dairy cattle - Miki SAKATANI; Kaiyu KUBOTA; Satoshi HAGA; Masafumi MIWA (The Society for Reproduction and Development, 2024)
Retained placenta (RP) adversely affects postpartum productivity and reproduction in dairy cattle. Thus, methods to predict the occurrence of RP before calving would be desirable. Herein, we assessed whether vaginal temperature measurements (which have already been applied to detect calving) could be used to predict the occurrence of RP in cattle. A vaginal temperature recording device was inserted into the vagina of 49 pregnant Holstein-Friesian heifers (n = 16) and cows (n = 33); this device recorded the vaginal temperature every 5 min until the device dropped out at calving. Serum was collected 10 days before the expected calving date. The time points of calving and placental expulsion were identified via video recordings. We further calculated calving duration (temperature decrease to calving) and placenta expulsion time (PE time = calving to placenta expulsion). The PE times were divided into four categories (0-4 h, 4-8 h, 8-12 h, and RP at >12 h), while subsequent analysis revealed that an extension of the PE time dependent on the shortening of the calving duration (P < 0.05). The vaginal temperature patterns also differed in a PE time-dependent manner, and cows with RP did not show any re-elevation of vaginal temperature. Serum analyses indicated an energy deficiency in RP cattle. These results suggest that RP may be detected early as a specific change in the vaginal temperature associated with reproductive hormone secretion.